An appropriation of Psalm 82 against the background of the Fourth Industrial Revolution. The Christian church as a change agent in the Fourth Industrial Revolution - Sutton, Lodewyk (HTS teologiese studies, 2020)
In an era during which more and more people show signs of narcissism, extreme individualistic views and a lack of empathy for others, the evidence that a definite change in society has taken place cannot be denied. This change is, in many ways, the result of the fast-growing pace of development and availability of technology, also known as the Fourth Industrial Revolution, in terms of which change has become a daily occurrence. Accessibility to the Internet and social media platforms contributes to the rapid change in society and how people and specifically younger generations view themselves and approach others. Amid this change, the church must act as a positive change agent and should not oppose change. Change has become a constant in the Fourth Industrial Revolution, and the church thus needs to become an agent in this process of change, to reorientate the focus of society and overcome the self-centeredness induced by current technological progress in society. What should such a focus look like? In answering this question, perspectives from Psalm 82 and the Old Testament are considered.Contribution: This article makes an interdisciplinary contribution, drawing knowledge from the Psalms in the Old Testament, social anthropology and technological advancement studies as to contribute on the relevance of theology today and the importance of understanding generational differences in a time of technological growth and the Fourth Industrial Revolution.